Iraq Sophism Recitation "luIIaby as example": أنمار علي حسين (Al-Academy, 2016)
The research consists of four chapters, and the research aims to uncover the melodic and rhythmic aspects of the Iraqi Sufi chanting (Thalilah as a model) as one of the models of Sufi chanting in Iraq that is held at the tomb of Sheikh "Abdul Qadir Al-Kilani". As for the temporal limit of the research, it is from 2011 to 2012.The researcher selected two samples for the research sample:1. Separation of the Thalilah of the Prophet Al Adnani2. Separate the chanting of prayersAccording to the musical analysis, the researcher prepared the search tool, which consisted of eight paragraphs, for a special standard system in line with the research objectives. The validity and reliability of the instrument was verified by experts to ensure its validity, and it was applied to two samples of the research, and after the musical analysis the researcher reached conclusions Advanced in this field, including:1. The wording of the thalilah depends on the first gender in the melody, which is the original name of which is called the thalilah chapter.2. Most of the rhythms performed in the chanting are embodied in the performance of the singers themselves, without any percussion instrument. The researcher also recommended a number of recommendations and proposals, and then translating the title and summary of the research into English